2018
DOI: 10.18203/2349-3933.ijam20181061
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary hypertension in COPD

Abstract: Background: Chronic obstructive pulmonary disease is a leading cause of morbidity and mortality in adults all over the world. Pulmonary hypertension (PH) is a severe disorder defined by a mean pulmonary artery pressure of ≥25 mmHg at rest. Pulmonary hypertension can occur as an isolated disease or as a consequence of a number of underlying diseases and conditions, such as heart failure and chronic obstructive pulmonary disease (COPD). The aim of our study was to study the prevalence of pulmonary hypertension i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…PAH was shown to be more common in study groups as COPD severity rose. Sruti Reddy et al [12], NK Gupta et al [13], and Vivek Katiyar et al [14] did similar research in India and found similar findings. COR-P was found in 20% of COPD patients as a reflection of pulmonary hypertension, with higher rates in severe and very severe illness.…”
Section: Resultsmentioning
confidence: 63%
“…PAH was shown to be more common in study groups as COPD severity rose. Sruti Reddy et al [12], NK Gupta et al [13], and Vivek Katiyar et al [14] did similar research in India and found similar findings. COR-P was found in 20% of COPD patients as a reflection of pulmonary hypertension, with higher rates in severe and very severe illness.…”
Section: Resultsmentioning
confidence: 63%